Pemeriksaan Angka Kuman Pada Daging Ayam Dengan Pemberian Parutan Rimpang Lengkuas Putih (Alpinia Galanga Linn Swartz) - Fatimah, Siti; Nadifah, Fitri; Azizah, Urfiyah Lisa (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Chicken meat is a good source of protein for daily consumption. It is very easy decayed biologically by enzymes or microbial spoilage. White galangal (Alpinia galanga Linn Swartz) is a kind of spice crop that can live in the highlands and lowlands. Generally, people utilize white galangal as a blend of seasoning. Galangal’s role as a food preservative is inseparable from its anti-microbial activity and secondary metabolite contents, i.e. essential oils. The anti-microbial is a biological or chemical compounds that could interfere the growth and activity of microbes, particularly microbes as a food spoilage. This research goal is to determine the number of bacteria in chicken meat with the provision granting the white grated galangal rhizome (Alpinia galanga Linn Swartz).This was a descriptive study with laboratory testing. We use pour plate method for the bacteria number determination. Independent variables is the indwelling time with grated white galangal for 1-5 hours and the dependent variable is the number of bacteria in chicken meat.The result showed that total number of bacteria after smeared with white grated galangal rhizome for 1 hour 463.500 CFU/gr, 2 hour 130.250 CFU/gr, 3 hour 58.250 CFU/gr, 4 hour 142.500 CFU/gr and 5 hour 302.500 CFU/gr. This study showed that grated white galangal has proven to reduce the number of bacteria in chicken meat.